2010
DOI: 10.4141/cjss09015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying appropriate methodology to diagnose aeration limitations with large peat and bark particles in growing media

Abstract: Caron, J., Morel, P., Rivie`re, L.-M. and Guillemain, G. 2010. Identifying appropriate methodology to diagnose aeration limitations with large peat and bark particles in growing media. Can. J. Soil Sci. 90: 481Á494. Large-sized particles (coarse peat, bark or sawdust) are often added to growing media to improve substrate aeration properties (gas storage and exchange). Recent studies have shown that large fragments mixed with fines may create barriers that restrict gas diffusion or create competition for oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
4
18
1
Order By: Relevance
“…The correlation matrix and the stepwise multiple regression analysis both suggested a significant effect of the gas exchange parameters ( D s D 0 −1 ) and pore effectiveness coefficient (γ) expected on the growth of seedlings for the prevailing wet conditions of 2009. Our results are thus very consistent with those of Allaire et al (1996), Nkongolo and Caron (2006a, 2006b), and Caron et al (2010) and were expected to some extent, given the wet water regime observed (Fig. 2b) and the lower air‐filled porosity of the substrates in 2009 than in 2008 (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The correlation matrix and the stepwise multiple regression analysis both suggested a significant effect of the gas exchange parameters ( D s D 0 −1 ) and pore effectiveness coefficient (γ) expected on the growth of seedlings for the prevailing wet conditions of 2009. Our results are thus very consistent with those of Allaire et al (1996), Nkongolo and Caron (2006a, 2006b), and Caron et al (2010) and were expected to some extent, given the wet water regime observed (Fig. 2b) and the lower air‐filled porosity of the substrates in 2009 than in 2008 (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…current selection criteria for peat in private and public nurseries are based on textural grades (i.e., diferent ratios of coarse and ine peat particles) because the particle size distribution has long been shown to afect the air-illed porosity (q a , a widely used substrate quality index; Carlson, 1983). he relationship between particle size and q a is still supported by most recent data (Caron et al, 2010).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Few studies have focused on the effect of root growth on growing media at the container scale, and the results have often been contradictory, probably due to different irrigation regimes and particle size distributions of the growing media used in these trials. All researchers have suggested that roots mainly grow in macropores and thus progressively fill them (Cannavo and Michel, 2013; Allaire‐Leung et al, 1999, Caron et al, 2010). In terms of aeration, this leads to a large decrease in air‐filled porosity (Caron et al, 2010; Cannavo et al, 2011; Cannavo and Michel, 2013), but the evolution of the pore tortuosity and of the resulting relative gas diffusivity are different.…”
mentioning
confidence: 99%
“…Oxygen stress may induce a number of reactions in plants, such as a reduction in transpiration, nutrient uptake and growth [5]. Recently the meaningfulness of air capacity as the most important parameter describing oxygen supply to roots is discussed in the literature [6][7][8][9]. The air in growing media contains oxygen, carbon dioxide, nitrogen and water vapor.…”
Section: Introductionmentioning
confidence: 99%